Rhythmic Alterations in Physiological Response, Growth Performance and Blood Metabolites in Growing Hariana Cattle Fed on Ration Included with Different Levels of Corn Silage - Verma, Ashwani Kumar; Kumar, Muneendra; Kumar, Vinod; Kushwaha, Raju; Vaswani, Shalini; Kumar, Avinash; Singh, Yajuvendra (Indian Journal of Animal Nutrition, 2020)
This study was conducted to determine the effect of green fodder replacement with corn silage on the physiological response, growth performance, and blood metabolites in summer exposed growing Hariana cattle. Eighteen growing Hariana cattle were randomly allocated into three groups (n=6) on body weight (130±3.0 kg) and age (14±1.5 months) basis. Experimental heifers either received a basal total mixed ration (TMR) devoid of corn silage (S0%) or were fed on TMR of which 50% (S50%) and 100% (S100%) green fodder were replaced with corn silage. Mean THI and RH values indicated that experimental heifers were in moderate heat stress. Replacement of green fodder with corn silage did not alter the physiological response of heifers during 90 d experimental periods. As the level of inclusion of corn silage increased, dry matter intake (DMI) and cost of feeding also increased (P<0.05) while average daily gain (ADG) was similar among all groups. Hematological attributes and plasma metabolites showed non-significant effect of green fodder replacement with corn silage. Although the green fodder replacement with corn silage increased cost of feeding but can be used as a best alternative during summer period by maintain the performance of dairy animals.